Co-expression of MyHC-15 with other known isoforms in rat muscle spindles - Vika Smerdu; Chiedozie Kenneth Ugwoke; Žiga Šink (European Journal of Histochemistry)
Muscle spindles are skeletal muscle sensory receptors composed of intrafusal fibres, partially encapsulated by connective tissue capsule. This capsule encloses the central A and B regions while leaving the distal C region extracapsular. Several past studies in rat have shown that muscle spindles typically contain a single bag1 fibre, a single bag2 fibre, and two smaller chain fibres. Intrafusal fibres co-express multiple myosin heavy chain (MyHC) isoforms: -slow or -1, -slow-tonic, -α, -2a, -2b, -embryonic, and -neonatal. While MyHC-2x was previously thought absent, the recently discovered MyHC-15 isoform has been identified in the C region of rat bag fibres. Using antibodies specific for nine MyHC isoforms and analyzing four different rat skeletal muscles—soleus, extensor digitorum longus, and the lateral and medial heads of gastrocnemius—we aimed to further characterize the co-expression pattern of MyHC-15 with other known isoforms and to determine whether MyHC-2x is expressed in rat intrafusal fibres. While rodents are widely used as animal models in skeletal muscle research, notable species-specific differences in MyHC isoform expression exist. Our findings revealed that MyHC-15 expression in rat intrafusal fibres is less abundant than in human fibres. MyHC-15 was primarily observed in bag fibres but was not detected in the C region, contrary to previous reports in both rat and human. We confirmed the absence of MyHC-2x in rat intrafusal fibres. Similarly, MyHC-embryonic and -neonatal were not detected in the analyzed spindles, suggesting that previously used antibodies may have cross-reacted with MyHC-2a and -2b. While our results partially corroborate previous extensive studies, discrepancies suggest that MyHC expression in intrafusal fibres varies not only along the fibre length but also across muscles.